Simpanan Berjangka Pada KSPPS BMT Amanah Ummah Menurut Fatwa DSN-MUI No. 02 dan 115 - Ditta Ayu Kurniasari Ekawardhani; Dian Filianti (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the application of Time Deposits in Sharia Financing Savings and Loan Cooperative (KSPPS) BMT According to Fatwa DSN-MUI No: 02 / DSN-MUI / IV / 2000 and Fatwa DSN-MUI No: 115 / DSN-MUI / IX / 2017 . In its application using mudharabah agreement that is cooperation contract between capital owner and entrepreneur in order to develop a business. In the development of the number of members of the term deposits did not increase as other savings products. so that needed research on its application.The results of this study indicate that in KSPPS BMT Amanah Ummah East Java the application of saving futures using mudharabah mutlaqah contract, while for members have given satisfaction and not yet attract other members to save their funds in time deposits. Implementation of the DSN-MUI fatwa No: 02 / DSN-MUI / IV / 2000 and the DSN-MUI fatwa No: 115 / DSN-MUI / IX / 2017 at KSPPS BMT Amanah Ummah East Java has been in conformity with Sharia principles. REFERENCESAl Qur’an dan Terjemahannya. 2014. Jakarta:Kementrian Agama RI.Ascaraya. 2008. Akad dan Produk Bank Syariah. Jakarta: PT Raja grafindo Persada.Fatwa DSN MUI No.02/DSN-MUI/IV/2000 Tabungan.Fatwa DSN MUI No. 115/DSN-MUI/IX/2017 Akad Mudharabah.Karim, Adiwarman. 2010. Bank Islam: Analisis Fiqih dan Keuangan, Edisi 4. Jakarta: PT. Raja Grafindo Persada.Lisdiwami, Indi Masita. Pengembangan Produk Funding KSPPS BMT Amanah Ummah Jawa Timur. Surabaya: Jurnal Ekonomi Syariah Teori dan TerapanMoleong, Lexy J.2011. Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya.Sudarsono, Heri.2004. Bank dan Lembaga Keuangan Syariah. Yogyakarta: Ekonisia.Yin, Robert K.2014. Studi Kasus: Desain & Metode. Jakarta: Grafindo.